2016
DOI: 10.4317/medoral.21189
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of total alloplastic temporo-mandibular joint replacement with two different types of prostheses: A three-year prospective study

Abstract: BackgroundTemporo-Mandibular Joint (TMJ) replacement has been used clinically for years. The objective of this study was to evaluate outcomes achieved in patients with two different categories of TMJ prostheses.Material and MethodsAll patients who had a TMJ replacement (TMJR) implanted during the study period from 2006 through 2012 were included in this 3-year prospective study. All procedures were performed using the Biomet Microfixation TMJ Replacement System, and all involved replacing both the skull base c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 17 publications
2
34
0
3
Order By: Relevance
“…For such cases, we think that the use of customised prostheses is essential. 12,13,17,20,25 In conclusion, the findings of this prospective clinical study have suggested that TMJ replacement with stock pros-theses is a safe, effective, and not unduly expensive procedure for joint reconstruction in cases with irreversible end-stage TMJ disease when there is sufficient bone available to allow proper stabilisation and fixation of the implant system. Improvement of functionality as well as reduction in pain persisted for five years after completion of the joint replacement.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…For such cases, we think that the use of customised prostheses is essential. 12,13,17,20,25 In conclusion, the findings of this prospective clinical study have suggested that TMJ replacement with stock pros-theses is a safe, effective, and not unduly expensive procedure for joint reconstruction in cases with irreversible end-stage TMJ disease when there is sufficient bone available to allow proper stabilisation and fixation of the implant system. Improvement of functionality as well as reduction in pain persisted for five years after completion of the joint replacement.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, the quality and quantity of bone varies considerably, meaning that fixation techniques must be suitable for different conditions. [11][12][13] In recent years, only a few systems have been available: the TMJ Concepts, the Zimmer-Biomet ® , and the Christensen System and now the Nexus CMF. Although it has been widely used, the latter has not been available since 2015 when the Food and Drug Administration withdrew its approval and, currently, there is only one stock model approved: the Biomet ® System.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there exist 44 models depending on different sizes and dimensions for the particular configuration of the Christensen implant. On the other hand, customised TMJR devices can be represented by the ultrahigh-molecular weight polyethylene (UHMWPE) on metal (Cr-Co) Biomet Microfixation TMJ Replacement System ® [12], being the glenoid fossa cup made of UHMWPE and the mandibular condyle of Cr-Co. Figure 1 depicts the 2 mentioned TMJR types, whereas the main characteristics and differences between stock and custom-made TMJ prostheses can be found in previous research works as [17].…”
Section: Introductionmentioning
confidence: 99%